2006
DOI: 10.1099/vir.0.81691-0
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 Tat prevents dephosphorylation of Sp1 by TCF-4 in astrocytes

Abstract: Previous examination of the effect of TCF-4 on transcription of the human immunodeficiency virus type 1 (HIV-1) promoter in human astrocytic cells found that TCF-4 affects the HIV-1 promoter through the GC-rich domain (nt "80 to nt "68). Here, the physical interaction and a functional consequence of TCF4-Sp1 contact were characterized. It was shown that expression of TCF-4 in U-87 MG (human astrocytic) cells decreased basal and Sp1-mediated transcription of the HIV-1 promoter. Results from a GST pull-down assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…It is also still likely that TCF-4 may bind Tat and that this complex binds to or near TAR, altering the stereochemistry of Tat-TAR interaction, leading to HIV inhibition or the formation of a multicomplex among TCF-4/␤-catenin, Tat, and TAR that leads to HIV inhibition. Recently it was also shown that TCF-4 interacts with the Sp1 transcription factor, which is one of the transcription factors that activate the HIV LTR, interfering with Sp1 LTR transactivation ability, in the absence of Tat (40). This interference could therefore result in lowered HIV gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also still likely that TCF-4 may bind Tat and that this complex binds to or near TAR, altering the stereochemistry of Tat-TAR interaction, leading to HIV inhibition or the formation of a multicomplex among TCF-4/␤-catenin, Tat, and TAR that leads to HIV inhibition. Recently it was also shown that TCF-4 interacts with the Sp1 transcription factor, which is one of the transcription factors that activate the HIV LTR, interfering with Sp1 LTR transactivation ability, in the absence of Tat (40). This interference could therefore result in lowered HIV gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…TCF-4 was shown to form a complex with Tat, presumably inhibiting Tat binding to transactivation response (TAR). More recently, TCF-4 was shown to interfere with Sp1 transcription factor, leading to modulation of its capability to activate the HIV LTR by binding to its cognate sites (40).…”
mentioning
confidence: 99%
“…Sp1 plays a critical role in many cellular events by regulating the expression of cellular genes. Tat activates Sp1 by phosphorylation of this protein, and thereby Sp1 proteins bind to LTR to upregulate the HIV-1 promoter (Chang et al, 1994;Rossi et al, 2006). The interaction of Tat with the HIV-1 accessory protein Vpr has also been shown to enhance the transcriptional activity of the HIV-1 LTR.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the RNA polymerase II complex, the phosphorylation of additional transcription factors, including Sp1, CREB, the alpha subunit of eukaryotic initiation factor 2 (eIF2a) and NF-kB have also been reported to be triggered by Tat (Demarchi et al, 1999;Li et al, 2005;Rossi et al, 2006;Zauli et al, 2001). Tat has been indicated to influence the HIV-1 promoter by phosphorylation of Sp1.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding acetylation of key Tat residues by the CBP/p300 complex enhances the subsequent engagement of Tat with the positive transcription elongation factor P-TEFb complex (12,18,19), composed of cyclin T1 and CDK9 subunits, permitting crucial phosphorylation of serine residues in the C-terminal domain (CTD) of RNAPII, resulting in complete viral gene expression (20). Additional phosphorylation events occur between Tat and cellular transcription factors, such as NF-B and Sp-1 (21,22), which play critical roles in the regulation of viral gene transcription. Subtype differences exist in the configuration of these and other transcription factor binding sites within the LTR, which have been reported to alter the responsiveness of HIV transcription to external stimuli: a single NF-B binding site is present in the promoter of HIV-1 subtype E (HIV-1E), yet subtype B contains two with subtype C containing at least three, but as many as four, NF-B consensus sequences (23).…”
mentioning
confidence: 99%